The Characteristics and Limits of Rapid Visual Categorization - Fabre-Thorpe, Michèle (Frontiers in Psychology, 2011)
Visual categorization appears both effortless and virtually instantaneous, the study by Thorpe et al. (1996) was the first to estimate the processing time necessary to perform fast visual categorization of animals in briefly flashed (20ms) natural photographs. They observed a large differential EEG activity between target and distrater correct trials that developed from 150 ms after stimulus onset. A value that was later shown to be even shorter in monkeys! With such strong processing time constraints, it was difficult to escape the conclusion that rapid visual categorization was relying on massively parallel, essentially feed-forward processing of visual information. Since 1996, we have conducted a large number of studies to determine the characteristics and limits of fast visual categorization. The present chapter will review some of the main results obtained. I will argue that rapid object categorizations in natural scenes can be done without focused attention and are most likely based on coarse and unconscious visual representations activated with the first available (magnocellular) visual information. Fast visual processing proved efficient for the categorization of large superordinate object or scene categories, but shows its limits when more detailed basic representations are required. Basic objects (dogs, cars) or scenes (mountain or sea landscapes) representations need additionnal processing time to be activated. A finding that is at odds with the widely accepted idea that such basic representations are at the entry level of the system. Interestingly, focused attention is still not required to perform such, more time consuming, basic categorizations. Finally we will show that object and context processing can interact very early in an ascending wave of visual information processing. We will discuss how such data could result from our experience with a highly structured and predictable surrounding world that shaped neuronal visual selectivity.